The Effect of Promotions and Wedding Package Prices on Sales Volume at Happy Bali Wedding - Ni Made Melia Prashanti Wahyuni; Luh Putu Citrawati; I Gede Sumadi (Journal of Event and Convention Management, 2023)
This study aims to examine the influence of promotion and wedding package pricing on sales volume at Happy Bali Wedding. The research employs a descriptive quantitative method using statistical approaches, including questionnaires and analysis through multiple linear regression, classical assumption tests, t-test, F-test, and the coefficient of determination (R²). The sample size consists of 74 respondents. The findings indicate that both variables—promotion (X1) and price (X2)—have a positive and significant effect on sales volume (Y), both partially and simultaneously. The regression model explains 95.8% of the variance in sales volume, while the remaining 4.2% is influenced by other factors not examined in this study.